Comparing maize storage technologies for managing post-harvest loss in Bako, Ethiopia - Tsegab Temesgen; Emana Getu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Ethiopian stored maize is expected to lose between 20 and 30% of its stock due to insect damage. To reduce these losses, Ethiopian farmers use chemically treated traditional storage structures and chemical-free Hermetic Storage Technologies (HSTs). We evaluated the storage techniques used in the area in this study. SPSS software was used to analyse the collected data, and mean differences were compared. The findings showed that after nine months of storage, maize stored in plastic containers, Purdue Improved Crop Storage (PICS) bags, chemically treated polypropylene bags, and chemically treated Goteras had grain damage of 4.83%, 5.65%, 56.83%, and 71.06%, respectively; the weight loss was 2.00%, 2.95%, 37.44%, and 56.87%. The percentage germination of maize grains stored in treated polypropylene bags and Goteras decreased from 55.33% to 48.48%, whereas maize contained in plastic containers and PICS bags dropped only slightly and was 98.83% and 95.80%, respectively. Insect development, maize grain damage, and weight loss were significantly reduced (p < 0.05) for plastic containers, PICS bags, chemically treated polypropylene bags, and treated Goteras. As a result, secure maize storage technology, such as hermetic storage technology, may alleviate poverty by increasing household income.